Understanding Financial Decision-making in Corporations: A Qualitative Inquiry into Leverage, Market Efficiency, and Financial Policy Implications - Puspitasari, Ayu; Muslim, M. (Manunggal Halim Jaya, 2024)
This qualitative inquiry delves into the intricate landscape of financial decision-making within corporations, aiming to shed light on leverage decisions, market efficiency dynamics, and financial policy implications. Employing thematic analysis, this study systematically reviews existing literature from academic databases, including PubMed, Scopus, Web of Science, and Google Scholar. The research synthesizes insights from peer-reviewed articles, books, and reports published within the past decade, employing rigorous inclusion and exclusion criteria to ensure relevance and credibility. The findings underscore the multifaceted nature of leverage decisions, revealing a complex interplay of factors such as tax policies, industry norms, and growth opportunities. Moreover, the significance of market efficiency in financial decision-making is confirmed, despite challenges to the assumptions of the efficient market hypothesis posed by anomalies in stock returns and behavioral biases among investors. Additionally, financial policy implications emerge as pivotal in guiding corporate operations, encompassing dividend policy, capital structure decisions, and environmental, social, and governance (ESG) considerations. The study advocates for a holistic understanding of financial decision-making processes, integrating insights from finance, economics, and sustainability. From a managerial perspective, the findings offer actionable insights for practitioners, emphasizing the importance of contextual factors, behavioral insights, and effective governance mechanisms in navigating the complexities of corporate finance. This research contributes to advancing knowledge in the field of corporate finance and provides guidance for practitioners, policymakers, and researchers in enhancing financial decision-making practices.